We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website.
Please click on "Accept cookies" if you agree to the setting of cookies. Cookies that do not require consent remain unaffected by this, see
cookie policy and privacy policy.
DECLINE COOKIES

When the polynomial P(x) = 6x3 + kx2 + x − 2 is divided by x + 2, the remainder is 0. Which of the following is also a factor of P(x)?

A:3x-1

B:3x+1

C:2x-1

D:x-1

Please help I am confused : )

Guest Mar 13, 2018

#1**+1 **

**When the polynomial P(x) = 6x ^{3} + kx^{2} + x − 2 is divided by x + 2, the remainder is 0.**

**Which of the following is also a factor of P(x)?**

**A:3x-1**

**B:3x+1**

**C:2x-1**

**D:x-1**

**polynomial long division:**

\(6x^3 + kx^2 + x - 2 : x + 2 = 6x^2+kx - 12x -2k+25 + \underbrace{\dfrac{4k-52}{x+2}}_{=0} \\ 6x^3 + kx^2 + x - 2 : x + 2 = 6x^2+kx - 12x -2k+25 + 0 \)

**remainder is 0:**

\(\begin{array}{|rcll|} \hline \dfrac{4k-52}{x+2} &=& 0 \\ 4k-52 &=& 0 \\ 4k &=& 52 \\ \mathbf{ k } & \mathbf{=} & \mathbf{13} \\ \hline \end{array}\)

\(\begin{array}{|rcll|} \hline 6x^3 + kx^2 + x - 2 : x + 2 &=& 6x^2+kx - 12x -2k+25 + 0 \quad & | \quad k = 13 \\ &=& 6x^2+13x - 12x -26+25 \\ &=& 6x^2+x -1 \\ &=& (3x-1)(2x+1) \\\\ \mathbf{ 6x^3 + kx^2 + x - 2 } & \mathbf{=} & \mathbf{(x+2)(3x-1)(2x+1)} \\ \hline \end{array} \)

**A:3x-1**

heureka Mar 13, 2018

#2**+1 **

When the polynomial P(x) = 6x3 + kx2 + x − 2 is divided by x + 2, the remainder is 0. Which of the following is also a factor of P(x)?

A:3x-1

B:3x+1

C:2x-1

D:x-1

If x+2 is a factor then f(-2)=0

so

\(P(2) = 6*(-2)^3 + k*(-2)^2 + (-2)− 2=0\\ 6*-8 + 4k-4=0\\ 4k=52\\ k=13\\ so\\ p(x)=6x^3+13x^2+x-2\)

If 3x-1 is a factor then x=1/3 will be a zero I can check this with the calcuator

6*(1/3)^3+13*(1/3)^2+(1/3)-2 = 0 **So (3x-1) IS a factor**

If 3x+1 is a facor then f(-1/3) = 0

6*(-1/3)^3+13*(-1/3)^2+(-1/3)-2 = -1.1111111111111111 No 3x+1 is not a factor

If 2x-1 is a factor then f(1/2)=0

6*(1/2)^3+13*(1/2)^2+(1/2)-2 = 2.5 No 2x-1 is not a factor

If x-1 is a factor then f(1)=0

6*(1)^3+13*(1)^2+(1)-2 = 18 No that isn't a factor either

I have determined this without any algebraic division.

Melody Mar 13, 2018